Bedürfnisse von Existenzgründern in der Gründungsphase - Susanne Durst; Michael Leyer (Frankfurt School of Finance & Management, 2011)
– Start-ups are a dominant factor for the economic development of a country. However, the foundation of a company is a complex procedure and many start-ups fail. External support is available from many sources as e.g. business angels, tax advisors, chambers of industry and commerce, banks and venture capitalists. Here, the main question is, which needs do the company founders really have and which external source is preferred for a support of these needs. To answer this question an empirical study was conducted, questioning company founders. The results show that the needs of company founders for external support are on an average level. If the company founders require external help, they prefer different sources. Thus, regional networks of different actors should be set up to support the process of setting up a company. This enhances the chances of the external actors and the company founder to set up a sustainable successful collaboration.
Keywords: D22; L26; M13; 330; entrepreneurship; analysis of needs; empirical study